2009
DOI: 10.1001/archfacial.2009.37
|View full text |Cite
|
Sign up to set email alerts
|

Graduated Approach to Refinement of the Nasal Lobule

Abstract: Our graduated approach has shown excellent outcomes, a high rate of patient satisfaction, and a low rate of revision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 21 publications
4
31
0
Order By: Relevance
“…In the present study and in the reference study, 10 Group 4 showed a larger number of patients. When the rate of patient satisfaction was assessed in relation to surgical outcome in each protocol group, differences were observed in prevalence between this study and the reference.…”
Section: 3supporting
confidence: 58%
See 4 more Smart Citations
“…In the present study and in the reference study, 10 Group 4 showed a larger number of patients. When the rate of patient satisfaction was assessed in relation to surgical outcome in each protocol group, differences were observed in prevalence between this study and the reference.…”
Section: 3supporting
confidence: 58%
“…10 When patients were distributed in the seven study groups, there was a predominance of females in all groups. The reference study 10 showed no gender distribution data between the groups for comparison with the present study.…”
Section: 3mentioning
confidence: 96%
See 3 more Smart Citations